Impact of Communication on Site Accidents Prevention: A Review - Musarat, M.A. (Institute of Electrical and Electronics Engineers Inc., 2021)
Occupational health safety is a moral and legislative obligation for every organization, and safety communication is a key factor that determines a positive and safe working environment. Usually, research conducted on safety management are focused on the causes and effects of an accident, however, the impact of communication on Health and Safety (HS) is seldom investigated. Thus, the purpose of this study is to evaluate the conducted study on the impact of safety communication on-site accident prevention. To achieve the study aim, 169 documents were extracted from Scopus based on keywords searching strategy. The keyword search criteria included the terms 'Accident' AND 'Communication' AND 'Prevention' AND 'Construction' within the year range from 2011 to 2021. Further, Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement was adopted, where 19 out of 169 studies were selected for detailed assessment. The detailed review of extracted articles revealed the impacts of communication on safety management. Moreover, digital technologies such as social network for sharing (SNSS), Mobile emergency response information system (MERIS), Voice communication and location services (VCLS), Mixed reality holographic application and their impacts on safety management were also discussed. The use of these innovative technologies can improve safety communication and safety outcomes. Â© 2021 IEEE.